Power Synchronization of Smart Transformers Allowing Universal Operation in Radial and Meshed Grids - Zhixiang Zou; Xingqi Liu; Jian Tang; Giovanni De Carne; Marco Liserre; Zheng Wang; Ming Cheng (CSEE Journal of Power and Energy Systems)
The Smart Transformer (ST) is a solid-state transformer with control and communication functionalities, interfacing medium voltage and low voltage grids. The ST can independently operate in a radial network configuration, and also in a meshed grid operation. The meshed operation has high potential to optimize the power flow in the network, avoiding or postponing the reinforcement of distribution grids. Nevertheless, the control and synchronization during the meshed operation are not trivial. The perturbation of the voltage in transition between the two operations is inevitable. This could lead to uncontrolled power flow and endanger the meshed operation. Moreover, the stability of the meshed grid has seldom been studied. To address these issues, this paper proposes a voltage control with power-based synchronization for the ST. This allows the universal operation of both radial and meshed grids, while ensuring smooth transition. Modeling and stability analysis of such a system are investigated to make sure of safe operation. Simulation and experimental results are provided to validate the effectiveness of the proposed control and theoretical analysis.